The Effect of Yoga Exercise and Cinnamon Aromatherapy to Reduction of Menstrual Pain Among Adolescent Girls at Azza Wajalla Health Vocational School, Bandar Lampung - Soraya Putria Ningsih; Dewi Yuliana; Yuli Lestari (LPPM STIKes Muhammadiyah Ciamis, 2026)
The effect of giving yoga exercise and cinnamon aromatherapy (Cinnamomum burmannii) on reducing menstrual pain in female adolescents at Azza Wajalla Health Vocational School, Bandar Lampung in 2025 is known. This study is a quantitative study with a pre-experimental one group pretest–posttest design. The study population was all 45 female adolescents in grades X–XI who experienced primary dysmenorrhea, with a sample of 32 students selected using a purposive sampling technique. The study was conducted at Azza Wajalla Health Vocational School, Bandar Lampung on December 10, 2025, to January 9, 2026. The analysis used the Wilcoxon test. The results of the analysis showed a p-value = 0.001 (<0.05), which means there is an effect of giving yoga exercise and cinnamon aromatherapy on reducing menstrual pain in female adolescents at Azza Wajalla Health Vocational School, Bandar Lampung in 2025.